The UN Decade of Ocean Science for Sustainable Development 2021–2030 - Vo, Si Tuan; Bui Thi , Minh Ha (Vietnam Journal of Marine Science and Technology, 2021)
The United Nations General Assembly declared the “United Nations Decade for Ocean Science for Sustainable Development, 2021–2030” in December 2017 to support the successful implementation of the Sustainable Development Goals (SDG), including SDG14 on seas and oceans. Drawing on IOC documents, the review provides background information on the Decade to help promote awareness and participation of Vietnam, a country that has actively committed to the 2030 Agenda of the United Nations. The United Nations Decade of Marine Science for Sustainable Development vision is “the science we need for the ocean we want”. Decade’s mission is to “promote the transformation of ocean science for sustainable development, connecting people and our oceans”. The Decade is geared towards seven socially desirable goals of a pollution-free, ecologically healthy, predictable, safe, productive, transparent, and understood ocean. The Decade’s perspectives and directions for action encourage the scientific community, public, and decision-makers to think beyond just doing business as usual and expect real change in the process of ocean understanding and collaborative management and partnerships to support sustainable development and maintain healthy oceans. During 2019–2020, the IOC, as the coordinating body, coordinated to prepare the implementation plan for the Decade, including the operating mechanism, the method of financial mobilization and management, and the process of evaluating the Decade’s performance results.